Preparation and Characterization of PANI Surface Modified HMX/F2602 Microcapsule Composites. Issue 10 (12th July 2022) - Li, Yuexin; Xu, Wenzheng; Guo, Fengwei; Yan, Tianlun; Zheng, Xin; Wei, Yamei; Tan, Xianpeng; Wang, Jingyu
Abstract: Using HMX with a particle size of 1–10 μm as the main explosive, a dense polyaniline (PANI) shell was prepared on the surface of HMX/F2602 by in situ polymerization, and an energetic composite material HMX−F@PANI (HMX−F2602@PANI) with a microcapsule structure was constructed. The structure and properties of the samples were characterized by SEM, XRD, XPS, DSC, mechanical sensitivity and electrostatic spark sensitivity tests. The results showed that the chemical structure and polycrystalline morphology of the crystals did not change during the coating process, and remained β‐HMX. The preparation of PANI shell greatly improves the coating degree of the explosive surface and reduces the exposure of crystal. In addition, compared with HMX/F2602, HMX−F@PANI is more excellent in improving thermal stability and reducing the electrostatic spark sensitivity, which is attributed to the advantages of microcapsule structure and good electrical conductivity of PANI. Abstract :